Accelerating Entrepreneurship Development in Fisheries Sector through Agribusiness Incubation - A, Razia Mohamed; Samuel, Manoj P; Ninan, George; N, Ravishankar C (Indian Farming, 2020)
Fisheries is sunshine sector of food production providing nutritional security, livelihood support and gainful employment to millions of people. Entrepreneurship is an important tool for promoting this sector and improving the economic development of a country. In this context the role of business incubators that supports the creation and growth of business through organizational and technical assistance, which at the same time contributes to the reduction of entrepreneurial failure, assumes great importance. The ZTM-ABI Centre operational at ICAR-CIFT manages technologies/ innovations, assists the entrepreneurs in seizing new business opportunities, and thus become key players in the growth of industries in fisheries and food processing sector.